Development of a three-pronged model for implementation of total quality management - Basmenj, Fazlollah Agamohamadi (2014)
One of the most significant current discussions with Total Quality Management (TQM) practices is achieving success from implementing of TQM in an organization. In an evolutionary process, researchers started from identification of TQM, TQM’s main factors and their effect, different applications, and now it needs more focus on certain TQM factors and their role in successful implementation of TQM. TQM has addressed as a management strategy or system in the recent research. In any case, the goals, how to achieve the goals and results, are subject to review procedures. This leads researchers to identify the main elements of TQM implementation, including Critical Success Factors (CSFs) as the goals, Quality Tools (QTs) as the actions and Performance Measures (PMs) as the results. Most existing research on TQM has examined the relationships between the two elements of TQM practices, or TQM as a single structure with one of the elements. There is a lack of examination of the relationships of the three main elements. According to literature, an arrangement between goals, actions and measures should be aligned to achieve better success rate. In this study, a three-pronged model for TQM implementation has been proposed. The relationships of three elements with each other were investigated to find the best way to perform TQM by identifying the most important elements of TQM and to classify them in the related division. In this regard, seven CSFs of TQM implementation were identified from the TQM literature. The QTs of TQM implementation were classified into four main groups based on literature to make the study possible. The PMs were studied by using five generic dimensions of performance related to quality management cited in literature. The empirical data for this study was drawn from a survey. Of 243 questionnaires delivered in Kuala Lumpur and Selangor area, 100 questionnaires were returned and used for the further analysis. Using the Simple Additive Weighting method (SAW), the relationship between three main elements of TQM implementation was analyzed. It ranks the effect of quality tools application to increase the critical success factors ability and to improve the performance measures of an organization. The obtained results from this step were aggregated to determine the rate of success in TQM implementation. Three viewpoints have been considered in the aggregation, to apply the quality tools, to increase the critical success factors ability, and to improve the performance measures. The results were validated by another independent data set collected from Iranian industries (central province-Arak) and a real case study. The study was able to propose a model, suggesting the best scenarios for successful implementation of TQM based on the goal of an organization. Therefore, this study has supported the premise of Dixon theory, which holds that a strategy can be implemented more successfully through the presence of aligned goals, action, and measures. Organizations will be able to achieve their objectives, including satisfying assumed critical success factors or improving supposed performance measures.